THE ROLE OF LINEAR PROGRAMMING LEARNING ACTIVITY USING MATHEMATICAL MODELLING - F Meta; Y Hartono; Hapizah Hapizah (Sriwijaya University Learning and Education International Conference, 2018)
This research is aimed at figuring out the role of learning activity using mathematical modelling in order to help pupils comprehend the linear programming. This research is conducted to the XI grade students of Xaverius 1 Palembang Senior High School. The learning implementation is conducted in XI Science class, which consists of 38 students. This research involves the mathematics teacher who acts as a model teacher to teach linear programming material. The method used in this research is the design research. The data are collected through video recording, taking picture during the learning process, students activity sheet, observation sheet, interview, and field notes during the learning process. The research result states that learning activity using mathematical modelling is benficial in providing the students opportunity to construct the linear programming knowledge by their own selves. Through independently thinking, students are given opportunity to express their idea about linear programming problem using mathematical modelling learning. Next, by asking the teacher, reading books, doing group discussion, and getting teacher’s reinforcement, the students are enable to enlarge the comprehension of linear programming.